EFFECT OF ORGANIC MANURES WITH RECOMMENDED DOSE OF NPK ON THE PERFORMANCE OF WHEAT (Triticum aestivum L.) - G. Abbas; J. Z. K. Khattak; A. Mir; M. Ishaque; M. Hussain; H. M. Wahedi; M. S. Ahmed; A. Ullah Adaptive Research Farm; Karor; District Layyah; Punjab; Pakistan. (Journal of Animal and Plant Sciences, 2012)
Recently, the interest in organic farming is increasing among the researchers and farmers due to the advent of high yielding cultivars and escalating fertilizer prices. Application of different organic manures in combination with inorganic fertilizer to wheat crop might give a substitute under field condition. A field experiment was conducted for two consecutive years (2007-09) with the objective to find out the best combination and type of organic and inorganic fertilizers for wheat (Triticum aestivum L.) production. The experiment was laid out in randomized complete block design (RCBD) with three replications. The treatments were: control (T1, no manure), departmental recommendation 128+114+62 NPK Kg ha-1 (T2), farmyard manure @ 10 tons ha-1 at time of seed bed preparation (T3), poultry manure @ 6 tons ha-1 + 128-114-62 Kg ha-1 NPK (T4). At maturity, plant height (cm), spike length (cm), number of spikelets per spike and grain yield from 1m2 area of randomly selected plants were recorded. Results led to the conclusion that T4 gave the best result with combination of 6 t/ha poultry manure + 128-114-62 kg ha NPK.
Keywords: Wheat; farmyard manures; NPK fertilizers; yield; Pakistan